2011
DOI: 10.1002/pon.2012
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy beliefs mediate the relationship between subjective cognitive functioning and physical and mental well‐being after hematopoietic stem cell transplant

Abstract: Objective Cognitive problems are commonly reported by hematopoietic stem cell transplant (HSCT) survivors, and are associated with poorer physical and mental well-being. It was hypothesized that adverse effects of subjective cognitive impairment occur because cognitive difficulties reduce survivors’ confidence that they can manage HSCT-related symptoms—that is, self-efficacy for symptom management. Methods HSCT survivors (n = 245) 9-months to 3-years post-HSCT completed measures of subjective cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
7
29
0
2
Order By: Relevance
“…Relationships were also affected; participants reported difficulties interacting with people due to diminished cognitive or neurobehavioral capacities (e.g., difficulty taking in a conversation), and changes in how people reacted to them because of those symptoms (e.g., loved ones getting annoyed with participant’s forgetfulness). These results corroborate findings from other studies that have highlighted the deleterious impact of self-reported cognitive impairments on quality of life (e.g., Hutchinson, Hosking, Kichenadasse, Mattiske, & Wilson, 2012; Wu et al, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Relationships were also affected; participants reported difficulties interacting with people due to diminished cognitive or neurobehavioral capacities (e.g., difficulty taking in a conversation), and changes in how people reacted to them because of those symptoms (e.g., loved ones getting annoyed with participant’s forgetfulness). These results corroborate findings from other studies that have highlighted the deleterious impact of self-reported cognitive impairments on quality of life (e.g., Hutchinson, Hosking, Kichenadasse, Mattiske, & Wilson, 2012; Wu et al, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Our findings must be interpreted as associations rather than causal relationships. Third, there are other possible contributing factors such as cognitive functioning, self-efficacy, self-esteem and health behaviors that were not addressed (9, 14, 59). Finally, we proposed pathways that are theoretically sound and testable per the availability of the dataset.…”
Section: Limitationsmentioning
confidence: 99%
“…However, deficits in one or more cognitive areas remained for more than 40% of survivors [45]. Subjective cognitive impairment in transplant patients has been associated with a reduction in survivors' confidence that they can manage symptoms post-treatment, with potential impact on overall physical and mental health [46]. Thus, interventions to improve self-efficacy with regard to cognitive function and self-management may be particularly useful for these patients.…”
Section: Cognitive Impairmentsmentioning
confidence: 99%